Beetles (Coleoptera) of Peru: A Survey of the Families. Attelabidae Billberg, 1820 - Legalov, Andrei A. (2019)
A new species, Omolabus (Sternolaboides) sokolovi Legalov n. sp. from Satipo, Central Peru, is described. New data for Hybolabus ater (Olivier, 1789), Omolabus (Perulabus) peruanus Legalov, 2004, O. (Pseudomolabus) westerduijni Legalov, 2008 and O. (Sternolaboides) ecuadorensis Legalov, 2007 are recorded. A verified species checklist of Peruvian Attelabidae based on literature and specimen examinations is presented. Distributions of 18 species from eight genera of two tribes found in the fauna of Attelabidae from Peru are given. Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:6C34BBEA-04C7-446B-8327-64F1A2FC0885Acto nomenclatural/nomenclatural act:LSIDurn:lsid:zoobank.org:act:F19261C5-A71F-48B1-B5C9-C868736B0AE9